Approaching Crime From A Psychological Perspective: Virtue Ethics And Criminal Etiology In Criminology - Nafis Dwi Kartiko (Activa Yuris: Jurnal Hukum, 2023)
This research aims to analyse the relationship between virtue ethics and criminal aetiology, particularly from a psychological perspective on criminal behaviour. Using the normative-dogmatic legal method, this research focuses on the systematic study of applicable legal rules and positive legal systems without collecting empirical data. The results indicate that virtue ethics has a significant influence on the prevention and reduction of criminal behaviour, showing that the formation of good character through moral education and positive behavioural examples can reduce the risk of criminal behaviour. This research contributes to the application of legal practice by suggesting the integration of virtue ethics principles for more effective rehabilitation and crime prevention strategies. The limitation of the research lies in the use of literature studies as the basis of analysis, which limits the generalisability of the findings to broader social practices.